The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/jocn.14968
|View full text |Cite
|
Sign up to set email alerts
|

Internationally qualified nurse communication—A qualitative cross country study

Abstract: Aims and objectives To compare the communication and practice experiences of migrant nurses in geographically distant, culturally dissimilar countries in Eastern and Western contexts. Background Considerable research has focused on the experience of acculturation of migrant nurses into geographically diverse locations. However, there remains scant comparative research which considers the ways in which migrant nurses interpret their experience through making “sense” of events encountered in their practice. Desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(39 citation statements)
references
References 37 publications
1
38
0
Order By: Relevance
“…The authors used a qualitative inquiry tool developed in New Zealand to examine the prevalence and impact of critical incidents in healthcare settings employing a multicultural nursing workforce (see Brunton & Cook, 2018). Brunton et al (2019) reported that although there were differences in the results of studies across New Zealand and the UAE, issues with language barriers, and the subsequent impact on nurse to patient and nurse to nurse relationships, were clearly evident in both studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors used a qualitative inquiry tool developed in New Zealand to examine the prevalence and impact of critical incidents in healthcare settings employing a multicultural nursing workforce (see Brunton & Cook, 2018). Brunton et al (2019) reported that although there were differences in the results of studies across New Zealand and the UAE, issues with language barriers, and the subsequent impact on nurse to patient and nurse to nurse relationships, were clearly evident in both studies.…”
Section: Introductionmentioning
confidence: 99%
“…Cross‐cultural communication presents unique issues for the art of nursing and the development of true presence between nurses and patients (Brownie et al, 2017; Brunton et al, 2019). After an extensive literature review, Brooks et al (2018) identified four defining attributes of successful and sensitive cross‐cultural communication that led to successful relationships with patients and families.…”
Section: Introductionmentioning
confidence: 99%
“…The 29 studies in which team processes are not the output investigate other types of cultural diversity outputs, namely, patient-related outcomes , for example, patient safety or quality of patient care (13 studies); team-related outcomes , for example, cultural competences within the team (four studies), team performance (five studies), team learning (three studies), and team climate (two studies); organizational outcomes , for example, cost efficiency (one study) and work climate (two studies); and individual outcomes , for example, understanding holistic care (one study; Schilgen et al, 2019), individual feelings of exclusion (one study; Brunton et al, 2019), discrimination (one study; Chamber & Alexis, 2004), minority team member isolation (one study; Dreachslin et al, 2000), and career advancement (one study; Chamber & Alexis, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Although CALD nurses help the current workforce meet societal demands and healthcare, extensive evidence has shown that these nurses undergo various challenges while integrating into work life (Buttigieg et al, 2018). These challenges have been found to impact their confidence, social life, and work satisfaction (Brunton et al, 2019), as well as impede their smooth integration into the workforce (Zanjani et al, 2021). In previous studies, organizational integration has been defined as the process through which CALD nurses overcome intra-organizational challenges and socialize to an organization (Ramji and Etowa, 2018).…”
Section: Introductionmentioning
confidence: 99%